Recent advances in controlling denitritation for achieving denitratation/anammox in mainstream wastewater treatment plants. (March 2020) - Ma, Bin; Xu, Xinxin; Wei, Yan; Ge, Chengjun; Peng, Yongzhen
Highlights: Denitratation/anammox is a promising method for anammox application in WWTPs. Denitritation is affected by biocommunity, pH and organic matter. Strategies for controlling denitritation are discussed. Processes for achieving denitratation/anammox in mainstream WWTPs are proposed. A denitratation/anammox application in a full-scale WWTP is documented. Abstract: Denitratation (NO3 − →NO2 − )/anammox is a promising method for anammox application in mainstream wastewater treatment plants (WWTPs) to reduce oxygen and organic matter consumption. Achieving nitrite production via denitratation and controlling denitritation (NO2 − →N2 ) is the basis of the denitratation/anammox process. To control denitritation, the denitrifying biocommunity and growth rate are critically reviewed for biocommunity optimization. Then, the short-term and long-term effects of pH on denitritation were summarized and the possible mechanism was discussed, along with the effect of C/N ratio and organic matter type on denitritation. Meanwhile, the strategies for producing nitrite via controlling denitritation are discussed, as well as the processes for achieving nitrogen removal via denitratation/anammox in WWTPs. Finally, the practical application of denitratation/anammox in a full-scale mainstream WWTP is documented.